2019
DOI: 10.1108/ejmbe-04-2019-0063
|View full text |Cite
|
Sign up to set email alerts
|

Anthropomorphized vs objectified brands: which brand version is more loved?

Abstract: Purpose The purpose of this paper is to deal with the role of the human metaphor (anthropomorphism) and consumers’ liking for the humanized version of the brand as antecedents of three key components of brand love: self-brand integration, positive emotional connection and feelings of anticipated separation distress. Design/methodology/approach A sample of 399 consumers provided information about a brand from a stated list of 16 brands of clothing. Findings Both anthropomorphism and consumers’ liking for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
0
9
0
4
Order By: Relevance
“…By introducing a novel construct of logo anthropomorphism this research contributes to the growing body of literature on brand anthropomorphism. Despite the growing volume of research on brand anthropomorphism there is a lack of agreement surrounding the measurement of its effects on consumer behaviour: some research has found positive effects (Aggarwal and McGill 2007;Delgado-Ballester, Palazón, and Peláez 2019;Rauschnabel and Ahuvia 2014), other research has found negative effects (Puzakova, Rocereto, and Kwak 2013;Kwak, Puzakova, and Rocereto 2015). Our research provides new insights to the testing of anthropomorphism in this context.…”
Section: Theoretical Implicationsmentioning
confidence: 80%
“…By introducing a novel construct of logo anthropomorphism this research contributes to the growing body of literature on brand anthropomorphism. Despite the growing volume of research on brand anthropomorphism there is a lack of agreement surrounding the measurement of its effects on consumer behaviour: some research has found positive effects (Aggarwal and McGill 2007;Delgado-Ballester, Palazón, and Peláez 2019;Rauschnabel and Ahuvia 2014), other research has found negative effects (Puzakova, Rocereto, and Kwak 2013;Kwak, Puzakova, and Rocereto 2015). Our research provides new insights to the testing of anthropomorphism in this context.…”
Section: Theoretical Implicationsmentioning
confidence: 80%
“…Ballester, dkk pada penelitiannya mengatakan bahwa, selain relasi kedekatan terhadap objek, desain visual sebuah objek yang mengalami antropomorfisme akan sangat berpengaruh kepada kecintaan konsumen terhadap objek [4]. Hal tersebut kemudian diperkuat oleh Wahab dan Nugroho bahwa teknik antropomorfisme yang dikombinasikan dengan gaya moe anime manga Jepang cocok jika ditargetkan pada pangsa pasar remaja [5], yang kemudian dibuktikan kembali oleh penelitian yang menyatakan bahwa gim populer Arknights juga menggunakan teknik desain karakter yang sama sebagai salah satu elemen penjual pada gaya desainnya.…”
Section: Pendahuluanunclassified
“…Antropomorfisme memiliki makna proses mengaitkan karakteristik, fitur, motivasi, niat, atau emosi mirip manusia dengan hal-hal yang bukan manusia, misalnya hewan, fenomena alam dan supernatural, benda, ataupun konsep abstrak. Penggunaan teknik antropomorfisme dengan desain yang tepat dan sesuai akan membuat sebuah desain dapat lebih diterima, dicintai dan disukai oleh konsumen [4].…”
Section: Hasil Dan Pembahasan Hasilunclassified
“…Consumer behavior research has explored various consequences of anthropomorphism from two perspectives. First, a majority of literature examines how anthropomorphism influences consumers’ attitude or reaction toward product or brand, such as changes in people’s attitude toward a brand (Aggarwal and McGill, 2007), brand evaluation after product wrong doings (Puzakova et al , 2013), persuasiveness of message (Touré-Tillery and McGill, 2015), risk perception (Kim and McGill, 2011), comparative judgment strategy (Huang et al , 2019), donation behavior (Zhou et al , 2018) and brand love (Delgado-Ballester et al , 2019). Second, the other cohort of studies investigate how anthropomorphism impacts consumer themselves, such as mitigation of social exclusion (Mourey et al , 2017) and consumer vitality (Chen et al , 2018).…”
Section: Anthropomorphism and Brand Anthropomorphism Scalesmentioning
confidence: 99%